DETERMINATION OF GASOLINE ATOMIZATION QUALITY UNDER THE SINUSOIDAL INERTIAL FORCES WITH IMAGE PROCESSING METHOD - Tanyerı, Burak; Atila, Orhan; Ucar, Ukbe; Öner, Cengiz (My University, 2022)
The atomization quality has gained importance with the used of injection systems in internal combustion engines. The atomization quality has been increased by raising spray pressures by the way advances in the production technologies of high-pressure pumps and injectors. In the current situation, the spray pressures in Gasoline Direct Injection (GDI) technology have been reached bar levels between 200 and 800. When the pressure level is raised higher than the specified pressure value, it is understood from studies in the literature that the atomization quality is not provided a significant improvement and the production cost increase due to the technology required for high pressure. In this paper, the fuel has been atomized by using Sinusoidal Intertidal Forces (SIF) as another method to improve the atomization quality. In the literature, there is no any study regarding the suitability of using by atomized under SIF of the gasoline fuel used in internal combustion engines. In the application study, the gasoline fuel has been atomized without the pressure by manufactured SIF generator and the droplet images obtained analysis result has been examined by using the image processing method. According to analysis results, it has been observed that the droplets sizes produced with SIF method were similar results to the droplet sizes founded using the GDI method. It has been determined that the smaller droplet sizes can be obtained with lower costs without using pressure thanks to this method and the method can be applied efficiently in internal combustion engines.
Keywords: Atomization Quality; Gasoline Direction Injection; Sinusoidal Intertial Forces; Droplet Size